2015
DOI: 10.1007/s10856-014-5355-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of an injectable bioactive bone filler cement with hydrogen orthophosphate incorporated calcium sulfate

Abstract: Calcium sulfate cement (CSC) has emerged as a potential bone filler material mainly because of the possibility of incorporating therapeutic agents. Delivery of the cement through a needle or cannula will make it more useful in clinical applications. However, it was not possible to make CSC injectable because of the inherent lack of viscosity. The present work demonstrates the design development of a viscous and fully-injectable CSC by incorporating hydrogen orthophosphate ions, which does not hamper the biocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Similar results were found by other researchers taking into account the dependence of the cement maturing i.e. setting time . Compressive strength for pure gypsum cements, is within the range determined by other researchers too .…”
Section: Resultssupporting
confidence: 91%
“…Similar results were found by other researchers taking into account the dependence of the cement maturing i.e. setting time . Compressive strength for pure gypsum cements, is within the range determined by other researchers too .…”
Section: Resultssupporting
confidence: 91%
“…Calcium sulfate has been generally regarded as bio-compatible [10,28,31,32]. However, many previous studies have also indicated that calcium sulfate lacks osteoinductivity [10,[32][33][34][35][36]. The present study demonstrates two important characteristics that support the bioactivity of a (Ca,Sr)SO 4 specimen.…”
Section: Bioactivity Of (Casr)sosupporting
confidence: 63%
“…One approach has been to add a bioactive agent. Peri-cement bone formation and/or in vitro osteoblastic responses have been improved with bioactive glass [51][52][53][54][55][56], hydroxyapatite [57], or other calcium-containing molecules [58][59][60][61][62][63][64]. These studies adopted the strategy of literally adding bioactivity to bone cement materials via additives, but this approach does not fundamentally improve material biocompatibility.…”
Section: Discussionmentioning
confidence: 99%